DO SOCIOECONOMIC AND DEMOGRAPHIC INEQUALITY IN BODY MASS INDEX VARY BY NUTRITION BEHAVIORS AND PHYSICAL ACTIVITY? THE CASE OF TURKEY - (:unkn) unknown (My University, 2021)
Differences in body mass index (BMI) is essential for public health policies. In this respect the objective of this paper is on inequalities in BMI across different nutrition behaviors and physical activities along with socioeconomic status and demographic characteristics. Data is from TURKSTAT Turkish Health Survey for the years 2014 and 2016. We control the differences in groups such as age, gender and family characteristics. We use education as the indicator of socio-economic status (SES). To answer how much of gap is due to nutrition and physical activity, we perform Blinder-Oaxaca type decomposition. Descriptive results show that probability of being obese or underweight decreases with level of education, individuals with low level of nutrition are more likely to be underweight, and individuals with high level of physical activity are less likely to become obese. According to decomposition results, physical activity accounts for the greater difference in mean BMI than nutrition when we control for education and demographic characteristics for females.

Vücut kitle indeksindeki (VKĠ) farklılıklar halk sağlığı politikaları için önemlidir. Bu bağlamda, bu makalenin amacı, sosyoekonomik durum ve demografik özelliklerin yanı sıra farklı beslenme davranıĢlarının ve fiziksel aktivitenin VKĠ‘inde yarattığı eĢitsizlikler üzerinedir. Veriler 2014 ve 2016 yıllarına ait TÜĠK Türkiye Sağlık AraĢtırması'ndan alınmıĢtır. ÇalıĢmada yaĢ, cinsiyet ve aile özellikleri gibi grup farklılıklarını da kontrol etmekteyiz. Eğitimi sosyo-ekonomik durumun göstergesi olarak kullanmaktayız. VKĠ‘indeki eĢitsizliğin ne kadarının beslenme ve fiziksel aktiviteden kaynaklandığını anlamak için Blinder-Oaxaca tipi ayrıĢtırma yapmaktayız. Betimsel sonuçlar eğitim düzeyiyle birlikte obez veya düĢük kiloda olma olasılığının azaldığını, düĢük beslenme düzeyine sahip bireylerin düĢük kiloda olma olasılığının daha yüksek olduğunu, yüksek fiziksel aktivite düzeyine sahip bireylerin de obez olma olasılığının daha düĢük olduğunu göstermektedir. AyrıĢtırma sonuçlarına göre, eğitim ve demografik özellikleri kontrol ettiğimizde, fiziksel aktivite, beslenme alıĢkanlıklarına göre kadınlarda ortalama VKĠ'indeki daha büyük farkı açıklamaktadır.
BESLENME ALIġKANLIKLARI VE FĠZĠKSEL AKTĠVĠTE, SOSYOEKONOMĠK VE DEMOGRAFĠK DEĞĠġKENLERE GÖRE VÜCUT KĠTLE ĠNDEKSĠ EġĠTSĠZLĠĞĠNĠ DEĞĠġTĠRĠYOR MU? TÜRKĠYE ÖRNEĞĠ